2021
DOI: 10.3389/fonc.2021.648978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients With Locally Advanced Gastric Cancer Who May Benefit From Adjuvant Chemoradiotherapy After D2 dissection: A Propensity Score Matching Analysis

Abstract: BackgroundOne of the most controversial areas in gastrointestinal oncology is the benefit of postoperative chemoradiotherapy (CRT) over chemotherapy (CT) alone after D2 dissection of locally advanced gastric cancer (LAGC). We aimed to identify the LAGC patients who may benefit from adjuvant CRT.MethodsWe analyzed retrospectively 188 patients receiving radical gastrectomy with D2 dissection for LAGC in our hospital. Patients were divided into two balanced groups by using propensity score matching: CRT group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our study found that N stage (pN3b) and NLR were independent prognostic factors for DFS in patients with LAGC after D2 dissection treated with chemoradiotherapy. In our previous study, we showed that pN3b is an independent adverse prognostic factor in gastric cancer after D2 dissection ( 24 ). Thus, in this study, we focused mainly on the correlation between NLR and the prognosis of patients with LAGC after D2 gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that N stage (pN3b) and NLR were independent prognostic factors for DFS in patients with LAGC after D2 dissection treated with chemoradiotherapy. In our previous study, we showed that pN3b is an independent adverse prognostic factor in gastric cancer after D2 dissection ( 24 ). Thus, in this study, we focused mainly on the correlation between NLR and the prognosis of patients with LAGC after D2 gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…All patients received 6 (range 4–8) cycles of treatment regimens involving fluoropyrimidine after surgery. Concurrent chemotherapy regimens included tegafur or capecitabine ( 24 ).…”
Section: Methodsmentioning
confidence: 99%